Optimalisasi Limbah Organik melalui Ecoenzyme dan Pengolahan Lele untuk Meningkatkan Kesejahteraan Masyarakat - Suwali Suwali; Ainun Faidah; Tiffany Rahma Abdillah; Shafira Agustin; Salsa Bila Aurora; Bintang Firly Baby Prasetyo (Institut Nalanda, 2026)
Household waste, particularly organic waste, remains an environmental issue that requires proper management. The ineffective management of organic waste in Candijati Village has the potential to cause environmental pollution. In addition, the community has potential in catfish farming that has not been fully utilized. This community service activity aims to enhance the knowledge and skills of the community in managing household waste through the production of ecoenzyme, its application in managing water quality for catfish cultivation, and the processing of aquaculture products into value-added products such as catfish crackers. The approach used is Service Learning, involving the community directly through training, practical activities, and mentoring. The results of the activity indicate an improvement in community understanding of organic waste management, as well as their ability to utilize ecoenzyme to improve water quality in aquaculture. Furthermore, the community is able to process catfish into crackers with higher selling value and has gained knowledge of product packaging techniques and marketing strategies.